Electrochemical Synthesis of Organoantimony Compounds and their Coordination Compounds - Rala, Sarbjit (Asian Journal of Chemistry, 2019)
Electrochemical reactions of bromoethane, 1-bromopropane, 1-chlorobutane and chlorobenzene have been carried out in acetonitrile at sacrificial antimony anode using tetrabutylammonium chloride as supporting electrolyte. The products isolated from the anode compartment have been characterized by elemental analysis and infrared spectral studies and are identified as organoantimony compounds. Coordination compounds of same have been synthesized with ligand (1,10-phenanthroline and 2,2'-bipyridyl). All these reactions proceed with high current efficiencies.